Imam Syafi'i's E-Commerce Concept's Relevance - A.Rio Makkulau Wahyu; Heri Irawan; Srianti Permata; Wirani Aisyah Anwar (Jurnal Ilmiah Ekonomi Islam, 2022)
Ba'i salam and e-commerce contracts are similar in that they involve the sale and purchase of goods with an upfront payment and subsequent delivery of goods up to a specified time limit. It is, however, significantly different because in a ba'i salam contract, the seller and buyer meet directly, whereas in e-commerce transactions, the buying and selling process is mediated by social media intermediaries. This type of research entails conducting library searches and data collection techniques that begin with reading references and end with classifying them in order to reach conclusions about the concept of relevance raised. E-commerce, in general, operates in the same way as the ba'i salam contract. The only distinction is the location of the contract. The distinction does not become critical, however, because bringing sellers and buyers together in one location is not an absolute, but rather a function of circumstances and conditions. When viewed through the lens of the ba'i salam contract, as interpreted by Imam Syafi'i and other scholars, the mechanism of buying and selling via e-commerce can be declared appropriate or conform to the conditions/rules established by Muamalah